Single-cell RNA sequencing reveals tumor immune microenvironment in human hypopharygeal squamous cell carcinoma and lymphatic metastasis - Li, Ce; Guan, Rui; Li, Wenming; Wei, Dongmin; Cao, Shengda; Xu, Chenyang; Chang, Fen; Wang, Pin; Chen, Long; Lei, Dapeng (Frontiers in Immunology, 2023)
Human hypopharygeal squamous cell carcinoma (HSCC) is a common head and neck cancer with a poor prognosis in advanced stages. The occurrence and development of tumor is the result of mutual influence and co-evolution between tumor cells and tumor microenvironment (TME). Tumor immune microenvironment (TIME) refers to the immune microenvironment surrounding tumor cells. Studying TIME in HSCC could provide new targets and therapeutic strategies for HSCC. We performed single-cell RNA sequencing (scRNA-seq) of hypopharyngeal carcinoma, paracancerous, and lymphoid tissues from five HSCC patients. Transcriptome profiles of 132,869 single cells were obtained and grouped into seven cell clusters, including epithelial cells, lymphocytes, mononuclear phagocytics system (MPs), fibroblasts, endothelial cells (ECs), plasmacytoid dendritic cells (pDCs), and mast cells. Four distinct populations were identified from lymphocytes, including B cells, plasma cells, T cells and proliferating lymphocytes. We found IGHA1 and IGHG1 specific plasma cells significantly overexpressed in HSCC tissues compared with normal hypopharygeal tissues and lymphatic tissues.Volcano chart and heatmap showed different genes of IGHG1 plasma cells and macrophage1 between HSCC tissues, adjacent normal tissues and lymphatic tissues. Five distinct populations from MPs were identified, including macrophages, monocytes, mature dendritic cells (DCs), Type 1 conventional dendritic cells (cDC1) and Type 2 conventional dendritic cells (cDC2). Subdivide of B cells, T cells, and macrophages cells and their distribution in three kinds of tissues as well as marker genes were also analyzed. SPP1+ macrophage was significantly overexpressed in HSCC tissues and lymphatic tissues compared with normal hypopharygeal tissues, which is thought to be M2type macrophages. We also studied proliferating lymphocytes, T cells exhausted, and T cell receptor (TCR) repertoire in HSCC tissues, adjacent normal tissues and lymphatic tissues. At last, we verified that IgA and IgG1 protein expression levels were significantly up-regulated in HSCC tissues compared to adjacent normal tissues. Overall, this study revealed TIME in HSCC and lymphatic, and provided potential therapeutic targets for HSCC.